Input-Output Analysis and the Cost Model: A Reply. - Gambling, Trevor (The Accounting Review, 1971)
Presents a response by Trevor Gambling to a letter to the editor about his article "A Note on Input-Output Analysis: Its Uses in Macro-Economics and Micro-Economics" that was published in the January 1970 issue of "The Accounting Review."